If at First You do Not Succeed: An Overview of Remedies Available in the United States Courts of Appeals - Thomas Allan Heller (LeXonomica, 2022)
In the United States federal court system, from a procedural standpoint, it has been the historic policy that appeals to the Courts of Appeal lie only from final decisions by the district courts.  This policy, dubbed the final judgment rule, is designed to prevent a piecemeal approach to appellate practice, and to enhance efficiency and fairness.  Applied overly strictly, the rule can often lead to unfair results, and even irreparable harm. This article catalogues the primary exceptions to the final judgment rule, and discusses those instances when interlocutory appeals may be taken short of district court rulings disposing of all issues as to all parties, that is, final judgments.Povzetek. V zveznem sodnem sistemu Združenih držav Amerike je bilo s procesnega vidika zgodovinsko sprejeto, da se pritožba na pritožbeno sodišče lahko vloži le zoper pravnomočne odločbe okrožnih sodišč. Namen te politike, imenovane pravilo pravnomočne sodbe, je preprečiti razdrobljen pristop k pritožbeni praksi ter povečati učinkovitost in pravičnost. Če se to pravilo uporablja pretirano strogo, lahko pogosto povzroči nepravične rezultate in celo nepopravljivo škodo. V tem članku so navedene glavne izjeme od pravila pravnomočne sodbe in obravnavani primeri, v katerih je mogoče vložiti vmesne pritožbe, če okrožno sodišče ni izdalo sodbe, s katero je odločilo o vseh vprašanjih za vse stranke, tj. pravnomočne sodbe.